Modulation of cortical vestibular processing by somatosensory inputs in the posterior insula. (December 2013) - Hashimoto, Teruo; Taoka, Miki; Obayashi, Shigeru; Hara, Yukihiro; Tanaka, Michio; Iriki, Atsushi
Abstract Primary objective: To study the mechanism of somatosensory-vestibular interactions, this study examined the effects of somatosensory inputs on body sway induced by galvanic vestibular stimulation (GVS) in healthy participants and persons with brain injury in the posterior insula, a region constituting a part of the parietoinsular vestibular cortex. Research design: This study adopted an experimental, controlled, repeated measures design. Methods and procedures: Participants were 11 healthy individuals, two persons with unilateral posterior insular injury and two age-matched controls. Bipolar GVS was applied to the mastoid processes while participants were sitting with their eyes closed, either lightly touching a stable surface with their index finger or not touching the surface with their index finger. Main outcomes and results: In healthy participants, tilting was greater with right hemispheric stimulation than with left hemispheric stimulation. Moreover, with right hemispheric stimulation, tilting was greater with a right finger touch than with no touch. The person with right-brain injury showed tilting induced by GVS; however, finger touch had no modulatory effect. In contrast, finger touch enhanced tilting in the person with left-brain injury. Conclusions: These preliminary results are discussed in light of a hypothesis of right hemispheric dominance of somatosensory-vestibular interactions in the posterior insula.